2022
DOI: 10.3390/antiox11112232
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Anxiolytic and Anti-Epileptogenic Potential of Lactuca Serriola Seed Using Pentylenetetrazol-Induced Kindling in Mice and Metabolic Profiling of Its Bioactive Extract

Abstract: This study aimed to assess the potential of Lactuca serriola (Asteraceae) seed n-hexane, chloroform, methanol, and aqueous extracts as anticonvulsant, sedative, anticonvulsant and antiepileptic agents in Swiss albino mice. Different doses of each extract were evaluated for the anxiolytic potential using the hole-board, the elevated plus maze and the light/dark test. A phenobarbitone-induced sleep test was employed for the evaluation of sedative potential. Acute anticonvulsant activity was evaluated by picrotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 62 publications
1
2
0
Order By: Relevance
“…The free radical can lead to seizure activity by inhibition of glutamine synthase and glutamate decarboxylase, thereby causing an abnormal accumulation of excitatory neurotransmitter glutamate (Diniz et al, 2015). The present result consisting with Ullah et al, (2022) who reported that PTZ induced oxidative stress in mice by decreasing CAT and increasing of MDA levels.…”
Section: Antioxidant Effects Of the Crude Flavonoids And Alkaloids Ex...supporting
confidence: 80%
“…The free radical can lead to seizure activity by inhibition of glutamine synthase and glutamate decarboxylase, thereby causing an abnormal accumulation of excitatory neurotransmitter glutamate (Diniz et al, 2015). The present result consisting with Ullah et al, (2022) who reported that PTZ induced oxidative stress in mice by decreasing CAT and increasing of MDA levels.…”
Section: Antioxidant Effects Of the Crude Flavonoids And Alkaloids Ex...supporting
confidence: 80%
“…root or Lactuca serriola (Asteraceae) can cause antiepileptic effects in pentylenetetrazole-induced seizure models ( Loshali et al, 2021 ). Among flavonoids, chrysin, resveratrol, baicalein, quercetin, and rutin produced significant anti-seizure activity or mild sedative and anxiolytic effects ( Ullah et al, 2022 ; Karioti et al, 2016). Thus, flavonoids can prevent neuronal excitability, suggesting their potential use as an adjunctive therapy for treating epilepsy.…”
Section: Phenols and Neuropsychiatric Disordersmentioning
confidence: 99%
“…′ -tetrahydronaphthalen-8carboxylic acid, confertin, scopoletin. [[265][266][267][268] [[269][270][271][272][273][274][275][276] Onopordum acanthium Antihypertensive, bactericide, cardiotonic, hemostatic agent, used against hypotonicity, anti-inflammatory, anti-malarial, anti-inflammatory, anti-tumor, cytotoxicity, antipyretic, analgesic, anti-tumor, regeneration, phytotoxic.Phenolic acids and derivatives: Isochlorogenic acid, caffeic acid, Flavonoids: Apigenin, luteolin, scutellarein, nepetin, chrysoeriol, hispidulin, pectolinarigenin, scutellarein 4 ′ -methyl ether, quercetin, apigenin-7-O-glucoside, apigenin-7-O-rutinoside, apigenin-7-O-β-D-glucuronide, luteolin-7-O-glucoside, quercetin-3-O-glucoside, isorhamnetin-3-O-glucoside, riodictyol; cyanin, aconiside. Others: Pinoresinol, syringaresinol, medioresinol, nitidanin diisovalerianate; arctiin, aesculin; aesculetin, 4β,15-dihydro-3-dehydrozaluzanin C, zaluzanin C, 4β,15,11β,13-tetrahydrozaluzanin C, onopordopicrin; arctiopicrin, Elemanolide 11(13)-dehydromelitensin β-hydroxyisobutyrate; acanthiolide, α-amyrin; β-amyrin, lupeol; taraxasterol, steroids, heptadecatetraen-(2,8,10,16)-diin-(4, 6)-al-(1), tridecadien-(1,11)-tetrain-(3,5,7,9), heptadecatetraen-(1,7,9,15)-diin-(11,13), heptadecatetraen-(2,8,10,16)-diin-(4,6)-ol-(1)), linoleic acid, oleic acid, palmitic acid, stearic acid, pentadecanoic acid, hentriacontanoic acid, nonacosanoic acid, arachidic acid, margaric acid, myristic acid, behenic acid, palmitoleic acid, gadoleic acid, erucic acid, vaccenic acids, α-tocopherol, α-tocotrienol, β-tocopherol, γ-tocopherol, 1-amino-2-propanol, stachydrine, choline, phytin.…”
mentioning
confidence: 99%